Boosting innovation through gender and ethnic diversity in management teams - Quintana-García, Cristina; Marchante-Lara, Macarena; Benavides-Chicón, Carlos Guillermo (Emerald, 2022)
Purpose: This study investigates the link between diversity in management and CEO positions and firm innovation. The purpose of this paper is to examine the effect that women and ethnic diversity in management and CEO positions have on the development of outstanding innovation in firms. Design/methodology/approach: This paper conducts an empirical analysis to investigate these relationships over time using a large panel database of 1,345 publicly US traded firms. Findings: Results revealed that gender and ethnic diversity at all levels of management exhibited a robust positive association with superior innovation competence. This finding remains robust when alternative proxies for innovation are employed. In contrast, the authors found that women and ethnic minorities at the CEO level had no significant influence. Originality/value: Considering an output measure of innovation, the authors explore the effect of gender and ethnic minority groups in management positions as well as at the CEO level, rather than focusing only on top management teams or board of directors. The authors offer new practical insights regarding the manager selection process that are also useful to support public policy initiatives.
Keywords: Identidad étnica; Igualdad de género; Diversity; Gender; Ethnicity; Innovation; Minority